Preliminary Note on the Debudding Trials on Pinus Longifolia in New Forest - Kadambi, K. (Indian Forester, 1954)
Height growth is not adversely affected by the annual debudding when compared to no debudding but the rate of growth is retarded if repeated debudding ( 4 times in a year) is done. Debudding increases formation of epicormics and becomes a difficult operation after some time.